2008
DOI: 10.1111/j.1365-2621.2007.01598.x
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of Listeria monocytogenes to materials commonly found in domestic kitchens

Abstract: The aim of this work was to investigate the adhesion of Listeria monocytogenes ATCC 15313 to glass, granite, marble, polypropylene from a bowl (PPb), polypropylene from a cutting board (PPcb) and stainless steel (SS), which are materials commonly used in kitchens. Marble and granite were chosen because they are applied as kitchen bench covers and pavements in many countries and there are no literature reports on their behaviour in terms of microbial adhesion. The effect of surface hydrophobicity and roughness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 27 publications
0
13
1
5
Order By: Relevance
“…20,29 Glass also has physicochemical surface properties similar to those of stainless steel: The free energies of adhesion (derived from surface-free energies from total, Lifshitz-van der Waals interactions and hydrogen bonds) of L. monocytogenes cells onto glass and stainless steel are almost identical 29 ; both materials are hydrophobic. 30 A microscopic glass slide (Fisher Scientific, Fair Lawn, NJ, USA) was cut into small pieces (22×22 mm). The piece was cleaned by immersing in 70% (v/v) nitric acid for 1 h, washed and rinsed with distilled water, sterilized with 70% (v/v) ethanol, and then dried for 10 min prior to use.…”
Section: Preparation Of Test Glass Surfaces and Bacterial Culturesmentioning
confidence: 99%
“…20,29 Glass also has physicochemical surface properties similar to those of stainless steel: The free energies of adhesion (derived from surface-free energies from total, Lifshitz-van der Waals interactions and hydrogen bonds) of L. monocytogenes cells onto glass and stainless steel are almost identical 29 ; both materials are hydrophobic. 30 A microscopic glass slide (Fisher Scientific, Fair Lawn, NJ, USA) was cut into small pieces (22×22 mm). The piece was cleaned by immersing in 70% (v/v) nitric acid for 1 h, washed and rinsed with distilled water, sterilized with 70% (v/v) ethanol, and then dried for 10 min prior to use.…”
Section: Preparation Of Test Glass Surfaces and Bacterial Culturesmentioning
confidence: 99%
“…Therefore, it is believed that the physical relief of surfaces favors bacterial adhesion, as do surface free energies. Stainless steel surfaces are thus prone to the formation of biofilms because of their great surface free energy, from which their hydrophilic characteristics derive [78]. In our study, it was found that both stainless steel and polyester surfaces without biocide were suitable for the adhesion and formation of biofilms, considering that polyester surfaces are much more porous and suitable for fixing microorganisms.…”
Section: Bacterial Count By Culture and Evaluation Of The Biofilm Formentioning
confidence: 58%
“…Moreover, ready-to-eat food, uncooked meat products, vegetables, poultry, and soft cheeses have all been reported as vehicles of listeriosis (Teixeira et al 2007b;Conter et al 2009;Jadhav et al 2012), with ingestion of contaminated food being the main route of transmission for humans (Dussurget 2008). Contamination of food by L. monocytogenes may happen through several distinct routes, such as staff equipment, uncooked materials, or contact surfaces (Møretrø and Langsrud 2004;Teixeira et al 2008). Nevertheless, as far as commercial foodstuff is concerned, contamination by these bacteria is not frequently a consequence of flaws in cleaning and disinfection, but it is due to cross-contamination in the post-processing environment (Ryser and Marth 2007;Latorre et al 2010).…”
Section: Main Foodborne Pathogensmentioning
confidence: 99%